2020
DOI: 10.1002/ange.202002757
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Molecular Iron Catalysts for Direct Photocatalytic Conversion of Formic Acid to Syngas (CO+H2)

Abstract: The catalytic decomposition of formic acid to generate syngas (a mixture of H2 and CO) is a highly valuable strategy for energy conversion. Syngas can be used directly in internal combustion engines or can be converted to liquid fuels, meeting future energy challenges in a sustainable manner. Herein, we report the use of homogeneous molecular iron catalysts combined with a CdS nanorods (NRs) semiconductor to construct a highly efficient photocatalytic system for direct conversion of formic acid to syngas at ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…− and H + , 3) the Fe(III) complex rapidly accepts the photogenerated electron from the excited CdS to produce Fe(II) species, 4) transfer of another electron from CO 2 − to Fe(II) species produces Fe(I) species which effectively reduce H + to yield H 2 (Irfan et al, 2020). In the present case, the immobilized FHS can act as a semiconductor photocatalyst enabling to both oxidize formate to produce H + and reduce H + to yield H 2 .…”
Section: Photocatalytic Decomposition/ Dehydrogenation Of Famentioning
confidence: 99%
“…− and H + , 3) the Fe(III) complex rapidly accepts the photogenerated electron from the excited CdS to produce Fe(II) species, 4) transfer of another electron from CO 2 − to Fe(II) species produces Fe(I) species which effectively reduce H + to yield H 2 (Irfan et al, 2020). In the present case, the immobilized FHS can act as a semiconductor photocatalyst enabling to both oxidize formate to produce H + and reduce H + to yield H 2 .…”
Section: Photocatalytic Decomposition/ Dehydrogenation Of Famentioning
confidence: 99%
“…Furthermore, the presence of Fe in the SAPO4-5 or TAPSO4-5 framework improves the redox properties of the catalysts and can shift their absorption spectra to the visible range, offering then an optimum band gap energy [29]. Moreover, it has been shown that the presence of Fe in photo-catalysts, significantly boosts their activity by suppressing the rapid recombination of photo-generated charge carriers [32].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 More importantly, the syngas product is a key intermediate than can be converted to bulk chemicals via Fischer-Tropsch processes. 11,12 Although 2nd-and 3rd-row transition-metal-based complexes (such as Re, Ir, and Ru) are considered to be the most capable catalysts for photocatalytic CO 2 reduction, their high cost and scarcity hinder their industrial-scale application. 13,14 In the past few decades, various photocatalysts, such as TiO 2 , g-C 3 N 4 , layered double hydroxides (LDHs), and CdS, have been investigated in detail for the photocatalytic reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%